The Impact of Obesity on the Association between Parity and Risk of Type 2 Diabetes Mellitus - Yuki Gen; Kyuho Kim; Joonyub Lee; Junyoung Jung; Sang-Hyuk Jung; Hong-Hee Won; Dokyoon Kim; Yun-Sung Jo; Yu-Bae Ahn; Seung-Hyun Ko; Jae-Seung Yun (Diabetes & Metabolism Journal)
Background Most studies focus solely on the relationship between parity and type 2 diabetes mellitus (T2DM) risk, providing limited insights into other contributing or protective factors. This study aims to explore the complex relationship between parity and T2DM risk, considering additional factors such as obesity, race, and body composition. Methods This prospective cohort study used data from 242,159 women aged 40 to 69 from the UK Biobank, none of whom had T2DM at baseline. Multivariable Cox proportional hazard models were applied to assess the association between parity and T2DM. Subgroup analyses were performed based on body mass index (BMI), waist circumference (WC), and race. Results The hazard ratio for T2DM per additional child was 1.16 (95% confidence interval, 1.13 to 1.16). Subgroup analysis revealed that Asian women and those with obesity or abdominal obesity had a higher risk of T2DM associated with multiparity. No increased risk was observed in women with normal BMI or WC. Mediation analysis showed that WC and BMI significantly mediated the parity-T2DM relationship, accounting for 49% and 38% of the effect, respectively. Conclusion There is a clear positive association between multiparity and T2DM risk, particularly in Asian women and those with obesity. Maintaining normal BMI and WC appears to mitigate this risk, highlighting the importance of weight management for women at higher parity levels. These findings offer crucial insights for public health interventions aimed at reducing T2DM risk among women.